2019
DOI: 10.1124/pr.119.017921
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensionality Data Analysis of Pharmacological Systems Associated with Complex Diseases

Abstract: large volumes of high-dimensionality data (e.g., transcriptomics, proteomics, metabolomics), it is now imperative that effective tools to appreciate this highly nuanced data are developed. Being able to appreciate the subtleties of high-dimensionality data will allow molecular pharmacologists to develop the most effective multidimensional therapeutics with effectively engineered efficacy profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 360 publications
(383 reference statements)
0
10
0
Order By: Relevance
“…This increase is related to the global epidemic of obesity and diabetes 6 . Because MetS not only increases the risk of diabetes, but also increases the risk of cardiovascular disease 7 , 8 , 9 , 10 , 11 , there is an urgent need to develop strategies to prevent this emerging global epidemic. Increasing studies have found that the pathogenesis and progression of MetS are closely related to inflammation 12 , and is usually called chronic low-grade inflammation, which interacts with insulin resistance and obesity 13 , and eventually worsens the MetS.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is related to the global epidemic of obesity and diabetes 6 . Because MetS not only increases the risk of diabetes, but also increases the risk of cardiovascular disease 7 , 8 , 9 , 10 , 11 , there is an urgent need to develop strategies to prevent this emerging global epidemic. Increasing studies have found that the pathogenesis and progression of MetS are closely related to inflammation 12 , and is usually called chronic low-grade inflammation, which interacts with insulin resistance and obesity 13 , and eventually worsens the MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Since a complex sequence of biological events seems to underlie the development of AD by arterial stiffness, it is very challenging to create an effective precision therapeutic treatment. Although precision medicine is still in its infancy, recent scientific efforts have already facilitated the elucidation of disease diagnosis and progression, as well as biomarker discovery through the combined use of "omics"-approaches and highdimensionality data analysis (Hendrickx et al, 2020b). Finally, we argue that different forms of inflammaging bridge arterial stiffness and AD and that their early detection is important to timely intervene in the devastating pathological aging present in arterial stiffness and AD.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 86%
“…One of the key features found within functional networks is the aspect of persistent homology 34 , in which repeating patterns are seen at multiple levels of network interrogation. To generate a multi-level interrogation of the initial metformin-associated DEP list (195 proteins), we assessed the latent text association of these proteins with concept terms aligned with the physiology of CKD and metformin treatment (i.e.…”
Section: Metformin Causes Differential Proteomic Expression Patterns ...mentioning
confidence: 99%